Automated Text Summarization and the SUMMARIST System - Hovy, Eduard; Lin, Chin-Yew (TIPSTER TEXT PROGRAM PHASE III, 1998)
This paper consists of three parts: a preliminary typology of summaries in general; a description of the current and planned modules and performance of the SUMMARIST automated multilingual text summarization system being built sat ISI, and a discussion of three methods to evaluate summaries.